Biblical Motifs in the Works of Nun Jefimija and Despot Stefan Lazarević: A Comparative Analysis - Kostić Tmušić, Aleksandra S.; Orlović, Tamara D. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
This paper examines biblical motifs in the works of Nun Jefimija and Despot Stefan Lazarević, with the aim of determining their function, meaning, and poetic role within Serbian medieval literature. Proceeding from the premise that the Bible constituted the fundamental spiritual and cultural foundation of medieval literary creativity, the study explores the ways in which these authors adopted and artistically shaped biblical symbols and themes. Particular attention is devoted to the works of Nun Jefimija, in which biblical motifs primarily serve a personal, devotional, and confessional function, as well as to Slovo ljubve (The Word of Love) by Despot Stefan Lazarević, where biblical symbolism acquires a didactic and moral dimension. Through a comparative analysis, the paper highlights both similarities and differences in the use of biblical motifs, shaped by the authors’ respective life circumstances and spiritual experiences. The study demonstrates that, despite their differing approaches, both writers employ biblical symbolism to express universal themes of suffering, faith, love, and hope for salvation, thereby endowing their works with enduring spiritual and literary value.
Keywords: biblical motifs; Serbian medieval literature; Nun Jefimija; Despot Stefan Lazarević; spirituality; symbolism